Adaptação transcultural para o Brasil de um instrumento sobre o conhecimento e as atitudes dos médicos diante da demência - Jacinto, Alessandro Ferrari [UNESP]; de Oliveira, Erika Correa; Citero, Vanessa de Albuquerque (FapUNIFESP (SciELO), 2015)
Objective: The aim of this study was to obtain a Brazilian transcultural adaptation of an instrument developed in the United Kingdom for assessing the knowledge and attitudes towards dementia by physicians. Methods: The “Knowledge Quiz” (KQ) contains 14 items on epidemiology, diagnosis and management of dementia, while the “Attitude Quiz” contains 10 sentences about physicians’ thoughts on the management of demented patients. The Quizzes were translated, back-translated and the resultant version applied to five physicians. Results: The transcultural equivalence process was performed and four items of the KQ needed adapting to the Brazilian context. After changes suggested by a panel of specialists, the final version was applied to another five physicians and the transcultural equivalence considered adequate. Conclusion: The Brazilian version of the instrument was successfully transculturally adapted for future validation and application in Brazil.
Brazilian transcultural adaptation of an instrument on physicians’ knowledge and attitudes towards dementia
Keywords: Aged; Dementia; Knowledge; Physicians